Pengaruh kinerja keuangan dan arus kas terhadap harga saham pada perusahaan kesehatan yang terdaftar di IDX - Muflihah, Fikrotul (Maliki Interdisciplinary Journal, 2024)
This study has a goal that is useful to determine the effect of financial performance and cash flow on stock prices. This research aims to use quantitative research methods as an aid in carrying out this research, and the data used in this research is financial report data taken from the IDX website regarding 5 health companies registered at IDX in 2020-2021. The results of this study are that financial performance has a significant effect on the stock prices of health companies listed on the IDX in 2020-2021, while cash flow has no significant effect on the stock prices of health companies listed on the IDX in 2020-2021. Keywords : financial performance, cash flow, stock price.